The Effect of Dayak Onion Bulb Ethanol Extract (Sisyrinchium palmifolium L.) on Triglyceride Level and Aorta Histopathology in Diabetes Melitus White Rat Induced by Alloxan - I Gusti Agung Ayu Kusuma Wardani; Fitria Megawati; Ni Made Dharma Shantini Suena (Faculty of Pharmacy, Universitas Gadjah Mada, 2019)
The high prevalence of diabetes mellitus in Indonesia has made antidiabetic treatment efforts increasingly popular. In addition, the many side effects caused by the use of chemical drugs, triggered the development of research on herbal therapy. The purpose of this study was to determine the effectiveness of Dayak onion bulb extract in reducing two-hour postprandial blood glucose, triglyceride levels, and the amount of lipid vacuoles in aorta blood vessels of diabetic rat. The long-term goal of this study is the creation of innovation products in the form of standardized herbs as complementary therapies that can be used daily by the community, so that the risk of morbidity can be reduced. The research design used was randomized control group pretest posttest design. The results of blood glucose analysis showed that there were significant differences between the positive control group with the 400 mg/KgBW and 800 mg/KgBW extract group, with a significance value of 0,000. In the extract group, 400 mg/KgBW with 800 mg/KgBW extract group showed no significant difference with a significance value of 0.390. The results of the analysis of triglyceride levels showed no significant difference between the positive control group with the 400 mg/KgBW extract group, with a significance value of 0.981. However, there were significant differences between the positive control group with the 800 mg/KgBW extract group with a significance value of 0.025. Between the 400 mg/KgBW and 800 mg/KgBW extract groups, there was a difference with a significance value of 0.024. Aorta histopathology results showed that there was a significant difference in the number of lipid vacuoles between the positive control group and the 400 mg/KgBW extract group and 800 mg/KgBW extract group. Based on the research, it can be concluded that the extract dose of 400 mg/KgBW is a dose that is able to influence the decrease in blood glucose levels, triglycerides and the amount of lipid vacuoles in the aorta blood vessels.